2021
DOI: 10.1016/j.omtn.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

MBD2 Mediates Septic AKI through Activation of PKCη/p38MAPK and the ERK1/2 Axis

Abstract: Our previous study demonstrated that the methyl-CpG-binding domain protein 2 (MBD2) mediates vancomycin (VAN)-induced acute kidney injury (AKI). However, the role and regulation of MBD2 in septic AKI are unknown. Herein, MBD2 was induced by lipopolysaccharide (LPS) in Boston University mouse proximal tubules (BUMPTs) and mice. For both in vitro and in vivo experiments, we showed that inhibition of MBD2 by MBD2 small interfering RNA (siRNA) and MBD2-knockout (KO) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…51 MBD2 was reported to activate 10 to 11 translocation 1 (TET1) and microRNA 200s (miR-200s) expression and induce apoptosis in lung adenocarcinoma cells, 52 and further studies have revealed that MBD2 promotes apoptosis of retinal cells 13 and renal tubular cells. 12,39,53 In the present study, we have found that loss of MBD2 protected AECs from LPS-induced apoptosis, to the best of our knowledge this is the first report that MBD2 could mediate apoptosis in AECs and lungs, which might provide a novel drug intervention target in future.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…51 MBD2 was reported to activate 10 to 11 translocation 1 (TET1) and microRNA 200s (miR-200s) expression and induce apoptosis in lung adenocarcinoma cells, 52 and further studies have revealed that MBD2 promotes apoptosis of retinal cells 13 and renal tubular cells. 12,39,53 In the present study, we have found that loss of MBD2 protected AECs from LPS-induced apoptosis, to the best of our knowledge this is the first report that MBD2 could mediate apoptosis in AECs and lungs, which might provide a novel drug intervention target in future.…”
Section: Discussionsupporting
confidence: 60%
“…38 Recently, Yuxin Xie et al reported that MBD2 promoted apoptosis of renal tubular cells, and MTF1 is one of the MBD2 targets involved. 39 In the present study, we have found that LPS treatment induced the expression of MTF1 and ZnT1 both in vivo and in vitro. Inhibition of MBD2 reduced MTF1 and ZnT1 levels, while the overexpression of MBD2 increased expression of MTF1 and ZnT1.…”
Section: Discussionsupporting
confidence: 55%
“…Besides, we conducted H&E staining analysis of renal tissues to examine the histological malformation of renal tissue in CLP‐induced sepsis mice. According to the previous study, 19 the percentage of damaged renal tubules was used to assess the score of tissue damage. The criteria of tubular damage included loss of brush border, tubular dilation, cast formation, inflammatory cell infiltration and cell lysis.…”
Section: Resultsmentioning
confidence: 99%
“…The liver histopathological scores were calculated as previously reported 18 . The renal tissue damage scores were calculated as previously reported 19 . Briefly, the percentage of damaged renal tubules was used to assess the score of tissue damage: 0, no damage; 1, <25% damage; 2, 25%‐50% damage; 3, 51%‐75% damage; 4, >75% damage, and the criteria of tubular damage included loss of brush border, tubular dilation, cast formation, inflammatory cell infiltration and cell lysis.…”
Section: Methodsmentioning
confidence: 99%
“…Referring to the methylation in TECs during sepsis, Xie et al ( 197 ) highlighted the function of methyl-CpG binding domain protein 2 (MBD2). They showed that knockdown of MBD2 in Boston University mouse proximal tubule (BUMPT) cells or global knockout of MBD2 in mice could significantly improve survival.…”
Section: Cellular Processes Interact With Programmed Cell Deathmentioning
confidence: 99%